Workers' participation and the French state, 1944-1948 - Steinhouse, A (1999)
This thesis explores attempts by state officials to enable workers and the principal trade union, the Confédération Générate du Travail, to participate at the workplace and in the French state from 1944 to 1948. At a time of increased state intervention and new social welfare policies, workers gained new responsibilities in the comités d'entreprises, or works councils. The regional government, the commissaires, helped to initiate worker control experiments, notably at the Berliet truck plant in Lyon. By the end of 1948, however, the strength of the French labour movement had not significantly increased, either at the workplace or in the state. In their demand for greater participation, workers faced resistance from state officials, employers and even unions. State actors, such as labour inspectors, prefects, and commissaires, actively sought social peace and greater productivity in 1944-1946. At the level of the shopfloor, the new comités d'entreprises gave workers, for the first time, an official voice in the firm. However, they had no say over production decisions. Nor did worker participation extend to unskilled workers, immigrants, or women. Worker participation did not go further at the time for three reasons. Employers intensified rationalisation measures at the workplace and refused to accept new powers given to the works councils. The CGT was insufficiently committed to workplace participation. Finally, the power of the centralised state was entrenched in the domain of economic planning but did not influence the workplace sufficiently to support participation, particularly in 1946-1948. The postwar settlement that led to increased growth in the 1950s was structured around the private sector and the planning capabilities of the state, at the expense of any involvement by labour. The exclusion of workers from planning decisions and the failure of worker control attempts led not only to the strikes of 1947-1948, but to a profound degree of powerlessness that was to mark the labour movement for the next generation.